From the Patient’s Perspective: The Impact of Training on Resident Physician’s Obesity Counseling - Jay, Melanie (Springer-Verlag, 2010)
BACKGROUND: It is uncertain whether training improves physicians’ obesity counseling. OBJECTIVE: To assess the impact of an obesity counseling curriculum for residents. DESIGN: A non-randomized, wait-list/control design. PARTICIPANTS: Twenty-three primary care internal medicine residents; 12 were assigned to the curriculum group, and 11 were assigned to the no-curriculum group. Over a 7-month period (1–8 months post-intervention) 163 of the residents’ obese patients were interviewed after their medical visits. INTERVENTION: A 5-hour, multi-modal obesity counseling curriculum based on the 5As (Assess, Advise, Agree, Assist, Arrange) using didactics, role-playing, and standardized patients. MAIN MEASURES: Patient-report of physicians’ use of the 5As was assessed using a structured interview survey. Main outcomes were whether obese patients were counseled about diet, exercise, or weight loss (rate of counseling) and the quality of counseling provided (percentage of 5As skills performed during the visit). Univariate statistics (t-tests) were used to compare the rate and quality of counseling in the two resident groups. Logistic and linear regression was used to isolate the impact of the curriculum after controlling for patient, physician, and visit characteristics. KEY RESULTS: A large percentage of patients seen by both groups of residents received counseling about their weight, diet, and/or exercise (over 70%), but the quality of counseling was low in both the curriculum and no curriculum groups (mean 36.6% vs. 31.2% of 19 possible 5As counseling strategies, p = 0.21). This difference was not significant. However, after controlling for patient, physician and visit characteristics, residents in the curriculum group appeared to provide significantly higher quality counseling than those in the control group (std β = 0.18; R(2) change = 2.9%, P < 0.05). CONCLUSIONS: Residents who received an obesity counseling curriculum were not more likely to counsel obese patients than residents who did not. Training, however, is associated with higher quality of counseling when patient, physician, and visit characteristics are taken into account.